(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The valley of Kashmir with an area of 222,236 sq Km located in the north of India falls in a very high seismic hazard zone. Kashmir has a recorded history of 5000 years and earthquakes form a big part of that history. The oldest remains of historic buildings are basically earthquake damaged ruins of temples and ancient universities. Because of the frequent occurrence of earthquakes, the people of Kashmir devised methods to live with the earthquakes. Later medieval structures in Kashmir show the emergence of one such method of lightweight construction with a combination of mud and brick that’s tied together by timber. This way structures were erected that could withstand earthquakes. This marks the beginning of a vernacular residential architecture in the valley of Kashmir that in our time is known as the Dhajji Dewari. The term “dhajji dewari” is derived from a Persian word meaning a patchwork quilt wall. This architecture was developed by using the material that was locally available making it easily adaptable to the culture, climate and natural environment of the Kashmir region. This striking architecture of the Kashmir valley, considered to be the architectural heritage of Kashmir, has over the last few decades has been considered as symbolic of poverty and has been rapidly replaced by the modern brick with cement-sand mortar form of construction that is constructed in a way which in the event of a high internist earthquake could prove disastrous. Present day plan of structures requires representing maintainability viewpoints utilizing a day-to-day existence cycle point of view, yet additionally the early plan stage where tremor activities have a huge impact concerning the foundational layout. As of late, the seismic assessment of stone work structures utilizing full scale component displaying approaches became well known, by applying execution-based evaluation methodology through nonlinear static (weakling) investigation procedures. This street numbers the approval for these methodologies alluding to two full scale workmanship structures tried under semi static sidelong stacking and practically obscure in the writing. The test conduct of tried unreinforced workmanship (URM) and confined masonry (CM) structures is thought about against the weakling reaction of the relating computational models. Then, at that point, alluding to ordinary lodging in southern Europe and its standard plan with a built-up concrete (RC) structure, the approved appraisal apparatuses are utilized to assess the quake safe prospects of URM and CM arrangements, in particular as far as greatest pertinent ground speed increases. The brick work arrangements are likewise analyzed as far as development costs against the RC typology. The considered examination instruments present a decent understanding while foreseeing, acceptably, the test conduct, along these lines having the option to be utilized in execution-based plan. Regarding the concentrated-on lodging, the anticipated sucker reactions for the stone work structures signify ability to oppose quakes sufficiently. These designs permit likewise a tremendous expense decrease (up to 25%) against the RC, hence seeming, by all accounts, to be contending choices. However, after the 2005 Kashmir earthquake this method of construction seemed intriguing to some researchers and for the first time proper researches were conducted on the construction method which showed very promising seismic resistance behavior by this construction method. This paper will attempt to breakdown the findings of those researches and draw suggestions and recommendations based on those findings.